Bioequivalence Study of Two Metformin Formulations - Hawari, Samar Al; AlGaai, Eman; Yusuf, Ahmed; Abdelgaleel, Abdelraheem; Hammami, Muhammad M. (Arzneimittelforschung, 2007)
A randomized single-dose cross-over study was conducted on 24 healthy male volunteers to compare the bioavailability of two metformin (CAS 657-24-9) tablet formulations, Emiphage™ (test) and a commercially available original preparation (reference). A dose of 850 mg was administered after an overnight fast with a washout period of seven days. Eighteen blood samples were collected over 32 h. Metformin concentrations in deproteinized serum were determined by a locally validated High Performance Liquid Chromatographic (HPLC) assay, and pharmacokinetic parameters were analyzed by the standard non-compartmental method.Mean Â± SD maximum concentration (Cmax), time to reach maximum concentration (Tmax), area under the curve (AUC0→t and AUC0→∞), and elimination half-life (t1/2) were 1.73 Â± 0.54 and 1.86 ± 0.67 µg/ml, 2.6 ±1.2 and 2.0 ± 1.0 h, 10.72 ± 3.93 and 10.82 ± 3.72 µg · h/ml, 11.53 ± 4.14 and 11.6 ± 3.84 µg · h/ml, and 3.1 ± 0.7 and 3.1 ± 0.9 h for the test and reference formulation, respectively. The parametric 90% confidence intervals on the mean of the difference (test - reference) between log-transformed values of the two formulations were 82.92% to 98.78%, 85.95% to 101.47%, and 77.82% to 100.4% for AUC0→t, AUC0→∞, and Cmax, respectively. The results indicate that the two formulations can be considered equivalent in the extent of absorption under fasting conditions.
Keywords: Antihyperglycaemic agent; Emiphage™; Metformin, bioavailability, bioequivalence, pharmacokinetics